Increased pain catastrophizing longitudinally predicts worsened pain severity and interference in patients with chronic pain and cancer: A collaborative health outcomes information registry study (CHOIR). Issue 10 (25th August 2022) - Wilson, Jenna M.; Schreiber, Kristin L.; Mackey, Sean; Flowers, K. Mikayla; Darnall, Beth D.; Edwards, Robert R.; Azizoddin, Desiree R.
Abstract: Objective: Little is known about how changes in psychosocial factors impact changes in pain outcomes among patients with cancer and chronic pain. This longitudinal cohort study of cancer patients investigated the relationships between changes in psychosocial factors and changes in pain severity and interference over time. Methods: Data from patients with cancer and chronic pain ( n = 316) treated at a tertiary pain clinic were prospectively collected. At their baseline visit (Time 1), patients provided demographic and clinical information, and completed validated psychosocial and pain assessments. Psychosocial and pain assessments were repeated at a follow‐up visit (Time 2), on average 4.9 months later. Change scores (Time 2‐Time 1) were computed for psychosocial and pain variables. Multivariable hierarchical linear regressions assessed the associations between changes in psychosocial factors with changes in pain outcomes over time. Results: Participants were an average age of 59 years, were 61% female, and 69% White. Overall, a decrease in pain severity ( p ≤ 0.001), but not pain interference, was observed among the group over time. In multivariable analyses, increased pain catastrophizing was significantly associated with increased pain severity over time ( β = 0.24, p ≤ 0.001). Similarly, increased pain catastrophizing ( β = 0.21, p ≤ 0.001) and increased depression ( β = 0.20, p ≤ 0.003) were significantly associated with increased pain interference over time. Demographic and clinical characteristics were not significantly related to changes in pain outcomes. Conclusions: Increased pain catastrophizing was uniquely associated with increased chronic pain severity and interference. Our findings indicate that cancer patients with chronic pain would likely benefit from the incorporation of nonpharmacological interventions, simultaneously addressing pain and psychological symptoms.